Miteinander statt nebeneinander! Strategien für die Weiterentwicklung interkommunaler Kooperationsstrukturen in der „Wiener Stadtregion+“ - Görgl, Peter; Döringer, Stefanie; Herburger, Johannes (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
The urban region of Vienna (Stadtregion+) is among the most dynamic growth regions in Europe. The management of the population growth poses extensive challenges for the city and its hinterland requiring a common and coordinated procedure. The urban regional cooperation structures are currently weakly institutionalised and barely defined. Against this background, this paper aims at presenting recommendations for the development of informal-cooperative spatial development processes in city regions on an analytical and instrumental level. The theoretical framework is based on a combination of the concept of strategic planning and the approach of soft spaces. The methods include the analysis of functional interconnections, a network analysis as well as the calculation of an interconnection index. By means of the “paradox of interconnection and cooperation” the totally different structures of the city-regional functional interconnections and the inter-municipal cooperation are shown on an analytical level. On an instrumental level, the planning principle of “flexible regionalisation” is presented, which draws upon and further develops the idea of spatial and temporal flexibility in strategic planning. A central element of this principle is the identification of “urban-regional focus areas” defined as specific areas within the urban region. These focus areas are characterised as soft planning spaces, in which to work on common planning and development challenges in an inter-municipal, cooperative and implementation-oriented manner. The applied methods and its findings are critically reflected and discussed, before deriving Vienna-specific and general policy recommendations.
Keywords: Urban region of Vienna; Cooperation; Soft Spaces; Functional Interconnections; Focus Area; Strategic Planning